Justice gained? : crime and crime control in South Africa's transition - Dixon, Bill; Van der Spuy, Elrena (UCT Press ; Willan, 2004)
Key questions in contemporary South African criminology are examined in these essays, including Why is crime such a persistent problem? and How have crime control practices altered in response to the challenges of the post-apartheid era?. Teachers, researchers, policy advisors, and practitioners challenge some of the received wisdom re-emerging in a discipline in danger of both forgetting its own history, and of misunderstanding the role of critical social science in a democratic South Africa.